Effect of Sublethal Dose/Concentration on Various Insect Behaviors - Victor George Siahaya (Agrologia, 2021)
Most of the studies on the impact of insecticides have always used acute toxicity with an indicator of death, whereas the lethal effect cannot fully determine the effect of the insecticide on insects. Overall, the effect of sublethal dose/concentration of insecticides can cause biological effects, disrupt egg number, laying period, larva and pupal weight, development period, life span and fertility rate, in addition to influencing feeding behavior, spawning period, locomotor system and reducing or increasing production and response to pheromones, physiological effects on the reproductive and immune systems and the nutritional status of insects. This suggests that the sublethal effect is very important to form the basis for analysis of insecticide risk. In addition, the sublethal effect also affects the presence of natural enemies and other useful insects, so it is hoped that more studies on their impact on non-target insects are expected.Keywords: biological effects, natural enemies, pheromones, sublethal effect